If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + -2(x + 2) = 3(x + -5) Reorder the terms: 4 + -2(2 + x) = 3(x + -5) 4 + (2 * -2 + x * -2) = 3(x + -5) 4 + (-4 + -2x) = 3(x + -5) Combine like terms: 4 + -4 = 0 0 + -2x = 3(x + -5) -2x = 3(x + -5) Reorder the terms: -2x = 3(-5 + x) -2x = (-5 * 3 + x * 3) -2x = (-15 + 3x) Solving -2x = -15 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -2x + -3x = -15 + 3x + -3x Combine like terms: -2x + -3x = -5x -5x = -15 + 3x + -3x Combine like terms: 3x + -3x = 0 -5x = -15 + 0 -5x = -15 Divide each side by '-5'. x = 3 Simplifying x = 3
| 8x-6-2x=34 | | 4.9(t^2)-24.5(t)-3=0 | | 3+4(2n-1)=6n-2 | | 10x-5y=-4 | | 5tanx+4=-1 | | 28=.5h(6+1) | | 18x+3(1-4x)=3(x+2) | | 5-(3+3lnx)=0 | | X^2+12x+2y^2+8y=3 | | 2+3lnx=0 | | 7x-24=5x+114 | | 7(1-x)+x=2-x | | 7(7x+5)=133 | | 2x-3+4x=-2x+7+3x | | 4(2y-1)-3=3-2y | | 5x^5-20x^4+5x^3+50x^2-20x-40=0 | | 7+(-3)=6+v | | x-0.08x=15 | | 2x-24=2x+48 | | (6,3)m=4/5 | | 5x-6(-4-12)=-189 | | x/5=31 | | v-(-6)=-3 | | 5a+2=6x-1 | | -(4y-3u-3)= | | 2f+3=11f+-24 | | 3p=-4 | | -2x-4-6y+15=-11 | | -2x-4-6y+15=11 | | -b/2(a) | | 9c=4 | | 6x/3x |